Sociological Analysis of Policies to Reduce Poverty and Social Inequality in Development Plans (Policy Solutions and Recommendations in Compiling the Seventh Development Plan - Amir Maleki (توسعه اجتماعی, 2023)
Combating poverty and social inequalities is always one of the main concerns of policymakers. In Iran, this issue has always been considered in the form of development plans and poverty alleviation bills. Unfortunately, the poverty indicators do not show satisfactory results. Considering the importance of the subject, in this article, the content analysis of six development plans has been done with an emphasis on policies to reduce poverty and social inequalities. The results indicate that; 1) In none of the development plans (except for the fourth plan), there is no standard and official poverty line used as a criterion for policymakers, 2) The most important challenge of development plans in poverty alleviation is "identifying the poor", 3) The poverty alleviation program in Iran mainly emphasizes on removing the consequences of poverty rather than its causes and roots, 4) the issue of vulnerability has not been given serious attention in the plans. Therefore, it is recommended to emphasize the following principles in preparing the seventh development plan: 1) at the beginning of the plan, a specific definition of the poverty line and the relevant indicators should be provided, 2) the target groups, namely the poor and deprived areas, and their needs should be identified, 3) Instead of a complication- based perspective, a structural approach to poverty should be adopted, 4) Instead of isolated programs, try to compile a comprehensive plan.